MEMBANGUN METODOLOGI PENELITIAN MATAN HADITS - Abdurrahman Said (JURNAL PUSAKA, 2013)
Hadith as a search data is a complicated job and need for a sufficient knowledge. As a data, the Hadith is an object of study already had an established methodology building, except the validity of the Matan. Not many references are trying to organize in a concrete methodology, except for some general criteria. As the data semantically, Matan has two side studies; lafdzÃ¬ and ma'nawÃ¬. This two associated with two criterion validity of the data Hadith; Syadz and 'illat. SyÃ dz research can only be done, if there are two or more conflicting data of hadith. And in illat conditions, the formulation of criteria for the data appear as â€œfalse hadithâ€, all of which are related to the condition of Matan.Keywords: Hadith Study, criterion validity, Matan of Hadith